Свобода слова в українській журналістиці: правові межі та правові дозволи - Подгорнова, А. Д. (ХНУРЕ, 2021)
Today, one of the most important human rights is the right to freedom of speech. The problem of freedom of speech is particularly acute in the context of the activities of Ukrainian journalists. Therefore, it is important to research and evaluate the provision of journalists with the right to freedom of thought and speech in Ukraine
Keywords: філософія; правові дозволи